1998
DOI: 10.1530/eje.0.1390023
|View full text |Cite
|
Sign up to set email alerts
|

Effect of small doses of iodine on thyroid function in patients with Hashimoto's thyroiditis residing in an area of mild iodine deficiency

Abstract: Objective: Several studies have suggested that iodine may influence thyroid hormone status, and perhaps antibody production, in patients with autoimmune thyroid disease. To date, studies have been carried out using large amounts of iodine. Therefore, we evaluated the effect of small doses of iodine on thyroid function and thyroid antibody levels in euthyroid patients with Hashimoto's thyroiditis who were living in an area of mild dietary iodine deficiency.Methods: Forty patients who tested positive for anti-th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
7

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 16 publications
(19 reference statements)
0
27
0
7
Order By: Relevance
“…This may indicate an additive effect of an increase in iodine intake and a surge in thyroid autoimmunity on thyroid failure in patients with SCH. Supplementary iodine given to individuals with euthyroid Hashimoto's thyroiditis has previously been associated with increased risk of a decline in thyroid function without change in thyroid autoimmunity (44), whereas serum TSH and TPO-Ab increased in some patients with euthyroid endemic goitre treated with potassium iodide (45).…”
Section: Correlations Of Serum Tsh To Other Biochemical Parametersmentioning
confidence: 99%
“…This may indicate an additive effect of an increase in iodine intake and a surge in thyroid autoimmunity on thyroid failure in patients with SCH. Supplementary iodine given to individuals with euthyroid Hashimoto's thyroiditis has previously been associated with increased risk of a decline in thyroid function without change in thyroid autoimmunity (44), whereas serum TSH and TPO-Ab increased in some patients with euthyroid endemic goitre treated with potassium iodide (45).…”
Section: Correlations Of Serum Tsh To Other Biochemical Parametersmentioning
confidence: 99%
“…Bournaud & Orgiazzi (27) reviewed the topic, and concluded that from a populationbased perspective iodine sufficiency favours occurrence of autoimmune thyroid disease, but the effect of iodine administration appears to depend on several factors, such as iodine status of the recipient, dose of administered iodine, degree of stimulation of the thyroid gland and genetic factors. Reinhardt et al (11) gave, in a randomised controlled study, a small amount of iodine to individuals with euthyroid Hashimoto's thyroiditis. The study subjects lived in a mildly iodine-deficient area.…”
Section: Serum Tsh Versusmentioning
confidence: 99%
“…In intervention studies, it has been found that excessive iodine intake may worsen hypothyroidism in individuals with autoimmune thyroiditis (11,12), and it may be speculated that variation in dietary iodine intake may influence thyroid function in patients with SH.…”
Section: Introductionmentioning
confidence: 99%
“…The sera were stored at -20°C and at the end of the study, they were transported frozen to Cardiff (UK) for autoantibody assay. Autoantibodies to Tg and to TPO were measured using a highly sensitive direct assay 6 and TSH receptor antibodies (TRAb) 7 assay. Serum TSH and free T 4 were also measured (Amerlite System).…”
Section: Methodsmentioning
confidence: 99%